KONJUNGSI DALAM FILM â€œSPIDERMAN: FAR FROM HOME KARYA McKENNA DAN SOMMERSâ€ - Nebuntu, Cowan; Pamantung, Rina P.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â This research is entitled â€œConjunction in the Film Spiderman: Far From Home by McKenna and Sommersâ€. It is a research which focuses on conjunction that uses in the film. Conjunction is a word that connects one word to another, one sentence to another, between clauses, and between phrases. Conjunction shows the relationship between sentence elements that connected. This purpose of this study is to identify, classify and analyse the forms and describe the meanings of conjunction found in the Film Spiderman: Far From Home by McKenna and Sommers. The theory that are used in order to obtain the results are by Aarts and Aarts (1982:44-45) about the form and John and Yates (1982:450) about the meanings. Hence, the results are show that the form of conjunction that used. In this research the writer found fourteen simple conjunctions; And (124), That (19), As (1), If (15), But (47), Or (8), Since (1), Then (1), While (2), For (6), Before (3), Because (28), Though (1), and Still (3), and one complex conjunction; As soon as. The meaning of conjunction that used in this reseach the writer found seven meaning of conjunctions: The conjunction indicates similar ideas, the conjunction indicates contrasting ideas, conjunction indicates results, conjunction indicates cause or purpose, conjunction indicates conditional ideas, conjunction indicates looseness ideas and conjunction indicates alternative ideas.————————–Keywords: conjunction, Film Spiderman: Far From Home by McKenna and Sommers